Molecular characterization of k-casein allelic variants in Bulgarian buffalo breed - Beneduci, Barbara; Krastanov, I.; Maretto, F.; Oblakov, N.; Cassandro, Martino (Acta Agraria Kaposváriensis, 2010)
This study aimed to analyze the genetic polymorphism at the k-CN (CSN3) locus in the Murrah Bulgarian buffalo breed. A 221 bp fragment of exon IV of CSN3 gene was amplified and sequenced to detect polymorphisms in 215 animals. Genotyping, by means of sequence alignments, revealed the presence of one polymorphism at codon 135 that occurs with a substitution of a Thr (ACC) of the A genetic variant for an Ile (ATC) of the B genetic variant, while codon 148 resulted monomorphic for the presence of an Ala residue (GCT). Additionally a silent mutation Thr-Thr (ACC/ACT) occurs at 136 codon position. Genotypes frequencies at codon 135 were 0.56 (AA), 0.40 (AB) and 0.04 (BB) being the gene frequencies 0.76 and 0.24 for the A and B allele respectively. No significant deviation from Hardy-Weinberg Equilibrium was observed.
Keywords: k-casein; genotyping; Murrah Bulgarian buffalo